2019
DOI: 10.3390/ijms20184429
|View full text |Cite
|
Sign up to set email alerts
|

IBR5 Regulates Leaf Serrations Development via Modulation of the Expression of PIN1

Abstract: Biodiversity in plant shape is mainly attributable to the diversity of leaf shape, which is largely determined by the transient morphogenetic activity of the leaf margin that creates leaf serrations. However, the precise mechanism underlying the establishment of this morphogenetic capacity remains poorly understood. We report here that INDOLE-3-BUTYRIC ACID RESPONSE 5 (IBR5), a dual-specificity phosphatase, is a key component of leaf-serration regulatory machinery. Loss-of-function mutants of IBR5 exhibited pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…The methods for GUS staining of ProOsARF6/17:GUS were modified from a previously published protocol (Kong et al, 2019). Briefly, lamina joints of flag leaf at different stages were incubated in GUS staining solution (50-mM NaPO 4 buffer, pH 7.0, 10-mg mL À1 X-Gluc, and 0.02% (v/v) Triton X-100), at 37 C in the dark for 12 h, and then washed with 70% (v/v) ethanol for 72 h twice until transparent.…”
Section: Gus Staining Procedures and Cell Wall Labelingmentioning
confidence: 99%
“…The methods for GUS staining of ProOsARF6/17:GUS were modified from a previously published protocol (Kong et al, 2019). Briefly, lamina joints of flag leaf at different stages were incubated in GUS staining solution (50-mM NaPO 4 buffer, pH 7.0, 10-mg mL À1 X-Gluc, and 0.02% (v/v) Triton X-100), at 37 C in the dark for 12 h, and then washed with 70% (v/v) ethanol for 72 h twice until transparent.…”
Section: Gus Staining Procedures and Cell Wall Labelingmentioning
confidence: 99%
“…The optimal expression of the genes is necessary for continuous growth and development. The miRNAs mainly contribute to the regulation of gene expression [ 45 , 195 ]. In leaf serration, the boundary controlling gene CUC1 , CUC2 , and CUC3 is required for the maintenance of the shoot apical meristem [ 45 , 195 ].…”
Section: Leaf Margins Serrationsmentioning
confidence: 99%
“…The miRNAs mainly contribute to the regulation of gene expression [45,195]. In leaf serration, the boundary controlling gene CUC1, CUC2, and CUC3 is required for the maintenance of the shoot apical meristem [45,195]. Furthermore, reports indicate that CUC2 has a very important role in leaf serration.…”
Section: Leaf Margins Serrationsmentioning
confidence: 99%
“…Arabidopsis typically has simple and small serrated leaves and is thus the ideal plant to study leaf shape and margin formation. Previous studies have shown that leaf serration formation depends on the guidance of auxin maxima at their tips ( Kawamura et al., 2010 ), and many proteins can regulate the leaf serrations of Arabidopsis by direct or indirect auxin process ( Kong et al., 2019 ). Auxin biosynthesis-related proteins, YUCCA (YUC), indole-3-acetic acid carboxyl methyltransferase (IAMT1), AUXIN-RESISTANT 1 (AUX1), and PIN-FORMED 1 (PIN1) ( Hay et al., 2006 ; Wenzel et al., 2007 ; Kim et al., 2011 ; Kasprzewska et al., 2015 ) can regulate the auxin maxima directly in the leaf tips for Arabidopsis .…”
Section: Introductionmentioning
confidence: 99%